A porous Pd / Ni composite electrode and its preparation and application in the electrosynthesis of H2O2
Patent Information
- Application Number
- CN202310393471.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-12
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-04-12
AI Technical Summary
现有技术中,2电子电催化合成H2O2的选择性和反应活性较低,贵金属利用效率低,且传统方法存在能量消耗高和安全隐患。
A porous Pd/Ni composite electrode is used. By preparing a zinc oxide nanotube array on a conductive substrate, Ni and Pd nanoparticles are electrodeposited using a constant current method to form a porous Pd/Ni nanotube array, which increases the active sites and disperses Pd atoms to form a self-supporting electrode.
It achieves highly selective and highly active H2O2 electrocatalysis, reduces the amount of precious metals used, improves the stability and economy of the electrode, and is suitable for on-site preparation of low-concentration H2O2 solutions.
Smart Images

Figure HDA0004176704310000011 
Figure HDA0004176704310000012 
Figure HDA0004176704310000013
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of electrochemical catalysis, specifically relating to a porous Pd / Ni composite electrode, its preparation method, and its application in the electrosynthesis of H2O2. Background Technology
[0002] Hydrogen peroxide (H2O2) has the advantages of being renewable and decomposing into non-toxic and pollution-free water and oxygen upon oxidation, making it widely applicable in daily life and industrial production, such as sterilization, pulp bleaching, and wastewater treatment. Currently, over 95% of hydrogen peroxide is produced using the multi-step, energy-intensive anthraquinone process. However, the anthraquinone process requires significant investment in basic equipment and facilities, consumes a lot of energy during production, and poses safety hazards during the transportation, handling, and storage of high-purity hydrogen peroxide produced by this process. In contrast, electrosynthesized H2O2 offers advantages such as mild reaction conditions and ease of on-site preparation. Electrosynthesized H2O2 can also be directly applied in various H2O2 application scenarios under specific conditions, with relatively low required H2O2 concentrations, such as in alkaline paper bleaching, wastewater treatment, and sterilization. H2O2 has great potential in medical sterilization and disinfection, and the on-site preparation of low-concentration H2O2 solutions for medical hand disinfection using electrosynthesis of H2O2 combined with appropriate equipment in an environment connected to pure water (or tap water) is an attractive research direction. Therefore, this method is considered a convenient, simple, and sustainable "green" H2O2 synthesis technology.
[0003] Since water is the thermodynamically most favorable product, oxygen may be reduced to water via a 4-electron pathway instead of hydrogen peroxide during the oxygen reduction reaction. This leads to the problem of low selectivity and reactivity in the 2-electron electrocatalytic synthesis of H₂O₂. Therefore, the current challenge in the 2-electron electrocatalytic synthesis of H₂O₂ is to develop electrocatalysts with high activity, high selectivity, and stability. The noble metal palladium (Pd) is currently the most efficient electrocatalyst for the 2-electron electrocatalytic synthesis of H₂O₂. How to fully utilize Pd atoms and reduce the amount of metallic Pd used is key to its large-scale application. Therefore, a carbon-supported Au... 1-x Pd x Nanoparticles exhibit high selectivity for H₂O₂. Furthermore, binary noble metal systems such as Pd-Ag and Pt-Hg have been shown in recent years to selectively reduce O₂ to H₂O₂. However, in such binary noble metal systems, only a small portion of the noble metal is exposed on the surface as active sites, significantly reducing the utilization efficiency of the noble metal; moreover, using toxic or other noble metals as the second metal is not environmentally or economically friendly. Therefore, a crucial prerequisite for using noble metal catalysts is the development of non-noble metal or non-metallic support matrices capable of dispersing the noble metal active centers and addressing the issue of 2e⁻.- ORR possesses noble metal active sites with excellent catalytic activity. Summary of the Invention
[0004] The purpose of this invention is to address the aforementioned problems by providing a porous Pd / Ni composite electrode with well-dispersed active sites and excellent catalytic effect, its preparation method, and its application in the electrosynthesis of H2O2. The porous Pd / Ni composite electrode is a porous Pd / Ni nanotube array, with the nanotube walls formed by the stacking of nanoparticles. This composite electrode exhibits excellent hydrogen peroxide selectivity, good stability, and a simple and effective preparation method. The entire synthesis process is green and controllable, which is highly beneficial for the mass production of this composite electrode.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0006] A method for preparing a porous Pd / Ni composite electrode includes the following steps:
[0007] 1) Fabrication of zinc oxide nanotube arrays on a conductive substrate;
[0008] 2) Using a conductive substrate with zinc oxide nanotube array as the working electrode, an auxiliary electrode is selected, and Ni nanoparticles are electrodeposited by constant current method to remove the zinc oxide template on the conductive substrate to obtain Ni nanotube array electrode.
[0009] 3) Using a Ni nanotube array electrode as the working electrode and selecting an auxiliary electrode, Pd nanoparticles are electrodeposited by a constant current method to obtain a porous Pd / Ni nanotube array electrode.
[0010] The electrodeposition conditions described in step 2) are a constant current density of 0.4–1 mA·cm⁻¹. -2 The deposition time is 5 min to 40 min.
[0011] In step 2), the electrolyte used for electrodeposition is a mixed solution containing nickel salt and ammonium salt. The nickel salt in the mixed solution is one or more of nickel sulfate, nickel chloride, and nickel nitrate, with a concentration of 0.01–0.03 M; the ammonium salt in the mixed solution can be one of ammonium chloride and ammonium nitrate, with a concentration of 0.02–0.05 M. The concentration of the ammonium salt is 1.5 to 2.5 times the concentration of the nickel salt.
[0012] Preferably, the concentration of the nickel salt is 0.02 M and the concentration of the ammonium salt is 0.04 M.
[0013] The removal of the zinc oxide template on the conductive substrate in step 2) is performed by acid removal, specifically a 0.01M to 0.1M HCl solution.
[0014] In step 3), the electrolyte used for electrodeposition is a PdCl2 solution with a concentration of 0.1 mM to 0.5 mM. The PdCl2 solution is prepared by acidification with hydrochloric acid at a concentration of 0.025 to 0.125 mM. The concentration ratio of hydrochloric acid to PdCl2 solution is 1:4. Hydrochloric acid is used for acidification because it can inhibit Pd... 2+ Hydrolyzes in solution.
[0015] The electrodeposition conditions described in step 3) are 0.25 mA to 0.5 mA·cm. -2 The deposition time is 15 min to 60 min.
[0016] The conductive substrate mentioned in step 1) can be one of nickel foam, carbon cloth, or titanium sheet. The titanium sheet used is a smooth titanium sheet obtained by grinding it with 400#, 800#, and 2000# sandpaper in sequence, and then cleaning the surface with anhydrous ethanol to remove the titanium oxide that has been removed by grinding.
[0017] The zinc oxide nanotube array described in step 1) is obtained by electrodeposition in an ammonium salt solution and alkaline etching.
[0018] The zinc oxide nanotube array is obtained through electrodeposition and alkaline etching. Specifically, a conductive substrate is used as the working electrode, an auxiliary electrode is selected, and zinc salt and ammonium salt are used as the electrolyte. Electrodeposition is performed, followed by alkaline etching, to obtain the zinc oxide nanotube array.
[0019] The concentration of zinc salt in the electrolyte is 0.005-0.02 M, and the concentration of ammonium salt is 0.04-0.06 M. Electrodeposition conditions: current density, 0.5-0.8 mA / cm². -2 The deposition time is 80-100 minutes and the temperature is 70-90℃.
[0020] The alkali used for alkaline etching is potassium hydroxide, sodium hydroxide, or ammonia, with a concentration of 0.01M to 1M, and an etching time of 24h to 48h.
[0021] The auxiliary electrode is a carbon rod.
[0022] The auxiliary electrodes mentioned in steps 2) and 3) are carbon rods or platinum sheet electrodes.
[0023] The electrodes obtained in steps (1), (2), and (3) should be rinsed with water and anhydrous ethanol in sequence and then air-dried naturally.
[0024] The porous Pd / Ni nanotube array composite electrode of this invention can electrocatalyze 2e in acidic, neutral, and alkaline systems. - Oxygen is reduced to produce hydrogen peroxide.
[0025] Experiments show that the porous Pd / Ni nanotube array composite electrode exhibits excellent electrocatalytic performance in generating hydrogen peroxide, with a maximum hydrogen peroxide Faradaic efficiency of approximately 86.5%. Furthermore, the electrode demonstrates good stability, enabling stable H2O2 production for 10 hours, with an H2O2 yield of 290.3 μmol.
[0026] Compared with the prior art, the present invention has the following advantages and effects:
[0027] (1) This invention provides a self-supporting porous Pd / Ni nanotube array composite electrode (nanotubes formed by stacking nanoparticles) through a simple electrodeposition method. The entire synthesis process is green, controllable, and easy to prepare.
[0028] (2) This invention uses zinc oxide templates to design Ni nanotube array structures, increasing the area of the nanoarray and thus increasing the active sites on the electrode surface. Furthermore, by using transition metal Ni as a carrier for the active center, the economic cost of electrode fabrication is reduced.
[0029] (3) Through precise control, Pd atoms are loaded on Ni nanotube array in a highly dispersed form by electrodeposition as isolated active centers. When O2 is adsorbed on the catalyst surface, it can be adsorbed on the active site of the catalyst in the form of "termination". This can effectively protect the OO bond from being destroyed and make oxygen highly selectively reduced to H2O2.
[0030] (4) The porous Pd / Ni nanotube array composite electrode prepared by the present invention has good electrocatalytic activity and exhibits advantages such as high hydrogen peroxide selectivity and high activity during the reaction process.
[0031] (5) The present invention prepares a self-supporting electrode with low Pd load and high performance of 2-electron electrosynthesis of hydrogen peroxide, which is expected to realize the application of on-site electrosynthesis of hydrogen peroxide in wastewater treatment and sterilization. Attached Figure Description
[0032] Figure 1 A schematic diagram of the synthesis of porous Pd / Ni nanotube array composite electrodes;
[0033] Figure 2 SEM image of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-2NTAs) prepared in Example 1;
[0034] Figure 3 TEM image and EDS spectrum of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-2NTAs) prepared in Example 1;
[0035] Figure 4The XRD patterns are of the porous Pd / Ni nanotube array composite electrodes prepared in Examples 1, 2, 3, and 4.
[0036] Figure 5 LSV diagrams of the porous Pd / Ni nanotube array composite electrodes prepared in Examples 1, 2, 3, and 4;
[0037] Figure 6 The LSV diagram, H2O2 Faradaic efficiency, and H2O2 yield of the porous Pd / Ni nanotube array composite electrode prepared in Example 2 are shown.
[0038] Figure 7 The H2O2 Faradaic efficiency and H2O2 yield of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-2NTAs) prepared in Example 1 in an H-type electrolytic cell;
[0039] Figure 8 Stability test of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-2NTAs) prepared in Example 1 at 0.3V;
[0040] Figure 9 The image shows a scanning electron microscope (SEM) image of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-2NTAs) prepared in Example 1 after a stability test at 0.3 V.
[0041] Figure 10 SEM image of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-1 NTAs) prepared in Example 2;
[0042] Figure 11 The porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-1 NTAs) prepared in Example 2 is used in an H-type electrolytic cell to measure the H2O2 Faradaic efficiency and H2O2 yield.
[0043] Figure 12 SEM image of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-3 NTAs) prepared in Example 3;
[0044] Figure 13 The porous Pd / Ni nanotube array electrode (Pd / Ni@ZnO-3NTAs) prepared in Example 3 is used to measure the H2O2 Faradaic efficiency and H2O2 yield in an H-type electrolytic cell.
[0045] Figure 14 SEM image of the Ni nanotube array electrode (Ni@ZnO NTAs) prepared in Example 4;
[0046] Figure 15 SEM image of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-4 NTAs) prepared in Example 5;
[0047] Figure 16 The images show the TEM and EDS spectra of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-4 NTAs) prepared in Example 5.
[0048] Figure 17 The image shows a scanning electron microscope (SEM) image of the porous Pd / Ni nanotube array composite electrode (Pd / Ni@ZnO-4 NTAs) prepared in Example 5 after electrochemical testing. Detailed Implementation
[0049] To better illustrate the purpose, technical solution, and advantages of the present invention, the following detailed description is provided in conjunction with the accompanying drawings and specific embodiments, but the implementation of the present invention is not limited thereto.
[0050] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.
[0051] Figure 1 This is a schematic diagram of the synthesis of a porous Pd / Ni nanotube array composite electrode.
[0052] Example 1:
[0053] A self-supporting porous Pd / Ni nanotube array composite electrode is prepared by the following steps:
[0054] (1) Cut the titanium sheet into 1*2cm pieces and polish them sequentially with 400#, 800#, and 2000# sandpaper until smooth. Clean the polished titanium sheet with ethanol and then soak it in a sealed mixture of ethanol and acetone for storage. Prepare a solution of 0.01M zinc nitrate and 0.05M ammonium nitrate as the electroplating solution. Pour 9mL of the prepared electroplating solution into a two-hole glass electrolytic cell with a frosted core. Adjust the temperature of the oil bath to 80℃ and place the polished titanium sheet (1cm deep) as the working electrode. Preheat the oil bath for 3 minutes and use a carbon rod as the auxiliary electrode. The current density is -0.8mA·cm. -2 Electrodeposition was performed for 5 minutes, followed by an electrodeposition at -0.5 mA·cm⁻¹. -2Electrodeposition was performed at a high initial current density for 90 minutes (the initial high current density was beneficial for the generation of abundant nuclei, while the subsequent low current density helped the zinc oxide grow uniformly). After the reaction, the titanium sheet was removed, rinsed with deionized water for 5-6 seconds, and allowed to air dry naturally. Then it was placed in 0.1M potassium hydroxide for 35 hours to obtain a hollow ZnO template.
[0055] (2) Prepare a mixed solution of 0.02M nickel chloride and 0.04M ammonium chloride as the electroplating solution for Ni nanoparticles. Pour 8 mL of the plating solution into a two-hole glass electrolytic cell with a frosted core. Use the titanium sheet electrode with a hollow ZnO template prepared in step (1) as the working electrode (immersed to a depth of 1 cm) and a carbon rod as the auxiliary electrode. At room temperature, adjust the potentiostat to -1 mA·cm. -2 The current density was set at -0.4 mA·cm⁻¹ for electrodeposition for 5 minutes. -2 Electrodeposition was performed at a high current density for 35 minutes (the electrodeposition process consists of two stages: nucleation and growth. The initial high current density is beneficial for the generation of abundant nuclei, while the subsequent low current density helps the nickel nanoparticles grow uniformly). After the reaction, the titanium sheet was removed, rinsed repeatedly with deionized water for 5-6 seconds, and allowed to air dry naturally. Then, it was immersed in 0.01M HCl for 10 minutes to remove the ZnO template, thus obtaining the Ni@ZnONTAs electrode.
[0056] (3) Using a 0.25 mM PdCl2 solution as the electroplating solution (the solution was prepared by acidification with hydrochloric acid, and the concentration ratio of hydrochloric acid to PdCl2 solution was 1:4), 8 mL of PdCl2 solution was poured into a two-hole glass electrolytic cell with a frosted core. The Ni@ZnO NTAs electrode prepared in step (2) was used as the working electrode (immersed to a depth of 1 cm), and a carbon rod was used as the auxiliary electrode. At room temperature, the potentiostat was adjusted to -0.25 mA·cm. -2 Electrodeposition was performed at a current density of 30 min. After the reaction was complete, the titanium sheet was removed, rinsed with distilled water for 5-6 s, and allowed to air dry naturally to obtain a porous Pd / Ni nanotube array composite electrode, denoted as Pd / Ni@ZnO-2NTAs.
[0057] See Figure 2 , Figure 2 This is a scanning electron microscope image of the porous Pd / Ni nanotube array composite electrode in Example 1.
[0058] See Figure 3 , Figure 3The images shown are transmission electron microscopy (TEM) images and EDS spectra of the porous Pd / Ni nanotube array composite electrode in Example 1. It can be seen that the porous Pd / Ni nanotube array composite electrode has a hollow tube structure, and the 111 crystal plane of Pd can also be observed, with a lattice spacing of 0.225 nm. The EDS spectra indicate that Pd and Ni elements are uniformly distributed on the porous Pd / Ni nanotubes.
[0059] See Figure 4 , Figure 4 The images show the XRD patterns of the porous Pd / Ni nanotube array composite electrode in Example 1 and in Examples 2, 3, and 4.
[0060] The porous Pd / Ni nanotube array composite electrode prepared in this embodiment was used as the cathode for the oxygen reduction reaction in the electrocatalytic synthesis of H2O2. An H-type electrolytic cell was used as the generator, a 1*1cm Pt sheet was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. Before the test, 40mL of water was used to prepare the electrode. -1 Oxygen was introduced at a flow rate of 15 minutes to saturate the electrolyte, and then the electrochemical performance of the three-electrode system was tested.
[0061] See Figure 5 , Figure 5 The images show the porous Pd / Ni nanotube array composite electrode in Example 1 and the LSV curves in Examples 2, 3, and 4.
[0062] The Pd / Ni@ZnO-2 NTAs prepared in Example 1 were used as the working electrode to test the LSV curve and electrolyze them for 1 hour at 0.4 V in electrolytes of 0.1 M HClO4, 0.1 M PBS, and 0.1 M KOH. The H2O2 concentration and Faradaic efficiency were determined using the conventional cerium sulfate titration method. Therefore, the Faradaic selectivity of Pd / Ni@ZnO-2 NTAs in 0.1 M HClO4, 0.1 M PBS, and 0.1 M KOH were 86.5%, 18.2%, and 12.5%, respectively. (See [reference needed]). Figure 6 .
[0063] Electrolysis of 0.1M HClO4 for 1 hour was performed at potentials of 0.5V, 0.4V, 0.3V, 0.2V, 0.1V, and 0.0V (relative to the standard hydrogen electrode). The Faraday selectivity of Pd / Ni@ZnO-2 NTAs reached 86.5% at 0.4V, and the H2O2 yield after 1 hour of electrolysis ranged from 15 to 36.4 μmol. (See [reference needed]). Figure 7Next, the porous Pd / Ni nanotube array composite electrode underwent a long-term stability test. The electrolysis potential was set to 0.3V, and the remaining apparatus and test conditions were consistent with the electrolysis test described above. H2O2 concentration was measured every two hours. After 10 hours of electrolysis, the porous Pd / Ni nanotube array composite electrode maintained a stable electrolysis current, with its Faradaic efficiency consistently above 81.5%, and H2O2 production reaching 290.3 μmol. (See [reference needed]). Figure 8 Furthermore, its morphology maintained a nanotube array after stability testing, as can be seen in [reference needed]. Figure 9 Therefore, Pd / Ni@ZnO-2 NTAs exhibit good stability.
[0064] Example 2:
[0065] A self-supporting porous Pd / Ni nanotube array composite electrode. The preparation method of the porous Pd / Ni nanotube array composite electrode in this embodiment differs from that in Example 1 in that the 0.25mM PdCl2 electroplating solution in step (3) is replaced with 0.1mM PdCl2, and the rest of the operation is the same as in Example 1. It is denoted as Pd / Ni@ZnO-1 NTAs.
[0066] See Figure 10 , Figure 10 This is a scanning electron microscope image of the porous Pd / Ni nanotube array composite electrode in Example 2.
[0067] The porous Pd / Ni nanotube array composite electrode prepared in this embodiment was used as the cathode for the oxygen reduction reaction in the electrocatalytic synthesis of H2O2. An H-type electrolytic cell was used as the generator, a 1*1cm Pt sheet was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. The electrolyte was 0.1M HClO4. Before the test, 40mL of the electrolyte was added. -1 Oxygen was introduced at a flow rate of 15 minutes to saturate the electrolyte, followed by a three-electrode system test. Electrolysis was performed for 1 hour at potentials of 0.5V, 0.4V, 0.3V, 0.2V, 0.1V, and 0.0V (relative to the standard hydrogen electrode), and the H2O2 concentration was determined using a conventional cerium sulfate titration method. The Pd / Ni@ZnO-1 NTAs showed a selectivity of 89.8% at 0.3V, and the H2O2 yield after 1 hour of electrolysis ranged from 6.1 to 24.6 μmol. (See [reference needed]). Figure 11 .
[0068] Example 3:
[0069] A self-supporting porous Pd / Ni nanotube array composite electrode. The preparation method of the porous Pd / Ni nanotube array composite electrode in this embodiment differs from that in Example 1 in that the 0.25mM PdCl2 electroplating solution in step (3) is replaced with 0.5mM PdCl2, and the rest of the operation is the same as in Example 1. Pd / Ni@ZnO-3 NTAs.
[0070] See Figure 12 , Figure 12 This is a scanning electron microscope image of the porous Pd / Ni nanotube array composite electrode in Example 3.
[0071] The porous Pd / Ni nanotube array composite electrode prepared in this embodiment was used as the cathode for the oxygen reduction reaction in the electrocatalytic synthesis of H2O2. An H-type electrolytic cell was used as the generator, a 1*1cm Pt sheet was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. The electrolyte was 0.1M HClO4. Before the test, 40mL of the electrolyte was added. -1 Oxygen was introduced at a flow rate of 15 minutes to saturate the electrolyte, followed by a three-electrode system test. Electrolysis was performed for 1 hour at potentials of 0.5V, 0.4V, 0.3V, 0.2V, 0.1V, and 0.0V (relative to the standard hydrogen electrode), and the H2O2 concentration was determined using a conventional cerium sulfate titration method. The selectivity of Pd / Ni@ZnO-3 NTAs reached 69.2% at 0.3V, and the H2O2 yield after 1 hour of electrolysis ranged from 15.1 to 42.5 μmol. (See [reference needed]). Figure 13 .
[0072] Example 4:
[0073] A self-supporting Ni nanotube array composite electrode is prepared by the following steps:
[0074] (1) Cut the titanium sheet into 1*2cm pieces and polish them sequentially with 400#, 800#, and 2000# sandpaper until smooth. Clean the polished titanium sheet with ethanol and then soak it in a sealed mixture of ethanol and acetone for storage. Prepare an electroplating solution of 0.01M zinc nitrate and 0.05M ammonium nitrate. Pour 9mL of the prepared electroplating solution into a two-hole glass electrolytic cell with a frosted core. Adjust the temperature of the oil bath to 80℃ and place the polished titanium sheet (1cm deep) as the working electrode. Preheat the oil bath for 3 minutes and use a carbon rod as the auxiliary electrode. The current is -0.8mA·cm. -2 Electrodeposition at a current density of 5 min was performed, followed by deposition at -0.5 mA·cm⁻¹. -2Electrodeposition was performed at a current density of 90 min. After the reaction, the titanium sheet was removed, rinsed with deionized water for 5–6 s, and allowed to air dry naturally. Then, it was placed in 0.1 M potassium hydroxide for 35 h to obtain a hollow ZnO template.
[0075] (2) Prepare a mixed solution of 0.02M nickel chloride and 0.04M ammonium chloride as the plating solution for Ni nanoparticles. Pour 8 mL of the prepared plating solution into a two-hole glass electrolytic cell with a frosted core. Use the titanium sheet electrode with a hollow ZnO template prepared in step (1) as the working electrode (immersed to a depth of 1 cm) and a carbon rod as the auxiliary electrode. At room temperature, adjust the potentiostat to -1 mA·cm. -2 The current density was set at -0.4 mA·cm⁻¹ for electrodeposition for 5 minutes. -2 Electrodeposition was performed at a current density of 35 min. After the reaction was complete, the titanium sheet was removed, rinsed repeatedly with deionized water for 5-6 s, and allowed to air dry naturally. Then, it was immersed in 0.01 M HCl for 10 min to remove the ZnO template, thus obtaining the Ni@ZnO NTAs electrode.
[0076] See Figure 14 , Figure 14 This is a scanning electron microscope image of the Ni nanotube array composite electrode in Example 4.
[0077] Example 5:
[0078] A self-supporting porous Pd / Ni nanotube array composite electrode is prepared by the following steps:
[0079] (1) Cut the titanium sheet into 1*2cm pieces and polish them sequentially with 400#, 800#, and 2000# sandpaper until smooth. Clean the polished titanium sheet with ethanol and then soak it in a sealed mixture of ethanol and acetone for storage. Prepare an electroplating solution of 0.01M zinc nitrate and 0.05M ammonium nitrate. Pour 9mL of the prepared electroplating solution into a two-hole glass electrolytic cell with a frosted core. Adjust the temperature of the oil bath to 80℃ and place the polished titanium sheet (1cm deep) as the working electrode. Preheat the oil bath for 3 minutes and use a carbon rod as the auxiliary electrode. (The process is described in the original text, but the context is unclear.) -2 Deposition was performed at a current density of -0.4 mA·cm for 5 min, followed by deposition at -0.4 mA·cm. -2 Electrodeposition was performed at a current density of 90 min. After the reaction, the titanium sheet was removed, rinsed with deionized water for 5–6 s, and allowed to air dry naturally. Then, it was placed in 0.1 M potassium hydroxide for 35 h to obtain a hollow ZnO template.
[0080] (2) Prepare a mixed solution of 0.02M nickel sulfate and 0.04M ammonium chloride as the plating solution for Ni nanoparticles. Pour 8 mL of the prepared plating solution into a two-hole glass electrolytic cell with a frosted core. Use the titanium sheet electrode with a hollow ZnO template prepared in step (1) as the working electrode (immersed to a depth of 1 cm) and a carbon rod as the auxiliary electrode. At room temperature, adjust the potentiostat to -1 mA·cm. -2 The current density was 0.4 mA·cm⁻¹, electrodeposition for 1 min, followed by -0.4 mA·cm⁻¹. -2 Electrodeposition was performed at a current density of 35 min. After the reaction was complete, the titanium sheet was removed, rinsed repeatedly with deionized water for 5-6 s, and allowed to air dry naturally. Then, it was immersed in 0.01 M HCl for 10 min to remove the ZnO template, thus obtaining the Ni@ZnO NTAs electrode.
[0081] (3) Prepare a 0.25 mM PdCl2 solution. Pour 8 mL of the prepared PdCl2 solution into a two-hole glass electrolytic cell with a frosted core. Use the Ni@ZnO NTAs electrode prepared in step (2) as the working electrode (immersed to a depth of 1 cm) and a carbon rod as the auxiliary electrode. At room temperature, adjust the potentiostat to -0.25 mA·cm. -2 At a current density of 10 ...
[0082] See Figure 15 , Figure 15 This is a scanning electron microscope image of the porous Pd / Ni nanotube array composite electrode in Example 5.
[0083] See Figure 16 , Figure 16 The images shown are transmission electron microscopy (TEM) images and EDS spectra of the porous Pd / Ni nanotube array composite electrode in Example 5. It can be seen that the porous Pd / Ni nanotube array composite electrode has a hollow tube structure. The EDS spectra indicate that Pd and Ni elements are uniformly distributed on the porous Pd / Ni nanotubes.
[0084] See Figure 17 , Figure 17 This is a scanning electron microscope (SEM) image of the porous Pd / Ni nanotube array composite electrode from Example 5 after electrolysis at 0.4V for 1 hour. Its morphology collapses after electrochemical testing.
Claims
1. An application of a porous Pd / Ni composite electrode, characterized in that: The porous Pd / Ni composite electrode is used for the electrocatalytic synthesis of H2O2; The porous Pd / Ni composite electrode is prepared by the following method: 1) Fabrication of zinc oxide nanotube arrays on a conductive substrate; 2) Using a conductive substrate with a zinc oxide nanotube array as the working electrode and selecting an auxiliary electrode, Ni nanoparticles are electrodeposited by a constant current method to remove the zinc oxide template on the conductive substrate, thus obtaining a Ni nanotube array electrode; the electrodeposition conditions in step 2) are as follows: during electrodeposition, the initial current is 0.9~1 mA·cm⁻¹. -2 Electrodeposition was performed at a current density of 4–6 min, followed by deposition at 0.4–0.7 mA·cm⁻¹. -2 Electrodeposition at current density for 20-40 minutes; In step 2), the electrolyte used for electrodeposition is a mixed solution containing nickel salt and ammonium salt; wherein the nickel salt in the mixed solution is one of nickel chloride and nickel nitrate, with a concentration of 0.01 ~ 0.03 M; the ammonium salt in the mixed solution is one of ammonium chloride and ammonium nitrate, with a concentration of 0.02 ~ 0.05 M; and the concentration of the ammonium salt is 1.5 to 2.5 times the concentration of the nickel salt. 3) Using Ni nanotube array electrode as working electrode and selecting auxiliary electrode, Pd nanoparticles are electrodeposited by constant current method to obtain porous Pd / Ni nanotube array electrode. In step 3), the electrolyte used for electrodeposition is a PdCl2 solution with a concentration of 0.1 mM to 0.5 mM. The electrodeposition conditions described in step 3) are: current density of 0.25 ~ 0.5 mA·cm⁻¹ -2 The deposition time is 15 min to 60 min.
2. The application according to claim 1, characterized in that: The concentration of the nickel salt is 0.02 M, and the concentration of the ammonium salt is 0.04 M.
3. The application according to claim 1, characterized in that: The removal of the zinc oxide template on the conductive substrate in step 2) is performed using an acid, specifically a 0.01 M ~ 0.1 M HCl solution. The conductive substrate mentioned in step 1) is one of nickel foam, carbon cloth, or titanium sheet.
4. The application according to claim 1, characterized in that: The zinc oxide nanotube array described in step 1) is obtained through electrodeposition and alkaline etching; Specifically, a zinc oxide nanotube array is obtained by using a conductive substrate as the working electrode, selecting an auxiliary electrode, using zinc salt and ammonium salt as electrolytes, electrodeposition, and then alkaline etching.
5. The application according to claim 4, characterized in that: During the preparation of zinc oxide nanotube arrays, The concentration of zinc salt in the electrolyte was 0.005–0.02 M, and the concentration of ammonium salt was 0.04–0.06 M. The electrodeposition conditions were: current density of 0.5–0.8 mA·cm⁻¹. -2 The deposition time is 80-100 minutes, and the temperature is 70-90℃; The alkali used for the alkaline etching is potassium hydroxide, sodium hydroxide, or ammonia, with a concentration of 0.01 M to 1 M, and the etching time is 24 h to 48 h. The auxiliary electrode is a carbon rod.
6. The application according to claim 1, characterized in that: The auxiliary electrode mentioned in steps 2) and 3) is a carbon rod or platinum sheet electrode; The electrodes obtained in steps 2) and 3) should be rinsed with water and anhydrous ethanol in sequence, and then air-dried naturally.
Citation Information
Patent Citations
Mn / Nano-G|foam-Ni / Pd combination electrode and preparation method thereof
CN103046072A
Nickel phosphide with nanotube array structure and preparation method and application of nickel phosphide
CN112779586A
